1995
DOI: 10.1128/jb.177.5.1186-1195.1995
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of the nitrogenase promoter in vitro: adenosine nucleotides are required for inhibition of NIFA activity by NIFL

Abstract: The enhancer-binding protein NIFA is required for transcriptional activation of nif promoters by the alternative holoenzyme form of RNA polymerase, which contains the sigma factor 54 ( N ). NIFA hydrolyzes nucleoside triphosphates to catalyze the isomerization of closed promoter complexes to transcriptionally competent open complexes. The activity of NIFA is antagonized by the regulatory protein NIFL in response to oxygen and fixed nitrogen in vivo. We have investigated the requirement for nucleotides in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
72
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 40 publications
(64 reference statements)
3
72
0
Order By: Relevance
“…The inhibitory activity of NifL is stimulated by adenosine nucleotides to promote formation of the NifL-NifA complex (5)(6)(7). This protein-protein interaction sequesters NifA and inhibits ATP hydrolysis by the activator, thus preventing productive interactions with 54 -RNA polymerase and inhibiting transcriptional activation at nif promoters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibitory activity of NifL is stimulated by adenosine nucleotides to promote formation of the NifL-NifA complex (5)(6)(7). This protein-protein interaction sequesters NifA and inhibits ATP hydrolysis by the activator, thus preventing productive interactions with 54 -RNA polymerase and inhibiting transcriptional activation at nif promoters.…”
Section: Resultsmentioning
confidence: 99%
“…Lanes 4,7,10,13,16,19, and 22 contained NifA, ATP, and 2-oxoglutarate incubated for t ϭ 0, 2, 6, 10, 30, 60, and 100 min, respectively. Lanes 5,8,11,14,17,20, and 23 contained NifA, ATP, and 3-oxoglutarate incubated for t ϭ 0, 2, 6, 10, 30, 60, and 100 min, respectively. Lane 2 shows purified NifA as a marker.…”
Section: -Oxoglutarate Binding To Gaf Domain Of a Vinelandii Nifamentioning
confidence: 99%
“…NifA-promoted catalysis of openpromoter complexes by 54 -RNA polymerase was used to assay NifA activity and its inhibition by NifL as described (16,18).…”
Section: Methodsmentioning
confidence: 99%
“…1). Unlike the HPKs, the GHKL domain of NifL does not exhibit ATP hydrolysis or transphosphorylation activity, but the binding of ADP to this domain strongly stimulates the inhibitory activity of NifL and the stability of the NifL-NifA complex (8,15,16). Also, the GHKL domain is involved in sensing the nitrogen status because it is the site of interaction with the signal transduction protein GlnK (17)(18)(19), the PII-like protein of A. vinelandii (20)(21)(22)(23).…”
mentioning
confidence: 99%
“…However, NifL and NifA are produced in roughly similar amounts, and coimmunoprecipitation tests suggested that they may form a complex (12). Also, total inhibition of NifA function in vitro requires a molar excess of NifL, either purified or reconstituted from inclusion bodies (9,20), so the action of NifL on NifA appears to be mediated by direct protein-protein interactions. If this is the case, a correct NifLNifA stoichiometry must be essential for regulation of nitrogen fixation, since synthesis of an excess of NifA could lead to a substantial production of many nif gene products under conditions in which they are unnecessary or useless.…”
mentioning
confidence: 99%